Stellenwert der PET/CT in der Lymphomdiagnostik - Afshar-Oromieh, Ali; Kratochwil, Clemens; Haberkorn, Uwe; Giesel, Frederik L. (Der Radiologe, 2012)
Clinical/methodical issueStaging or re-staging of lymphomas using conventional imaging modalities is based on morphological changes, usually on the diameter of lesions. However, vitality of tumors cannot be evaluated.Standard radiological methodsIn this context computed tomography (CT) has been used as a standard modality.Methodical innovationsSince the introduction of positron emission tomography (PET), evaluation of tumor vitality has become possible. Moreover PET/CT hybrid scanners were brought onto the market one decade ago.PerformanceThe fluorodeoxyglucose (FDG) PET/CT technique is now accepted as one of the most accurate modalities in the diagnosis of aggressive lymphomas due to a high FDG uptake (overall accuracy > 90%, sensitivity >90%). However, indolent lymphomas suffer from lower FDG uptake due to a moderate metabolic activity. After the introduction of PET/CT hybrid imaging the specificity of this diagnostic technique increased significantly compared to PET alone (from > 80% to > 90%). With the utilization of PET approximately 20% more lesions are detected when comparing to CT alone and in up to 15% of the patients this also results in a change of the therapeutic regime. As post-chemotherapy scar tissue usually persists for months, evaluation of vitality within residual bulks using FDG-PET can predict therapy response much earlier than CT, enabling therapy stratification. Other PET tracers apart from FDG have low impact in imaging of lymphomas and only the thymidine analogue fluorothymidine (FLT) is used in some cases for non-invasive measurement of proliferation.AchievementsDespite the capability of FDG-PET/CT there is no evidence that the improvement in diagnostics is translated into a better patient outcome and therefore warrants the high costs. False positive findings in PET can result in unnecessary treatment escalation with subsequent higher therapy-associated toxicity and costs.Practical recommendationsSome pitfalls can be avoided by scheduling PET scans carefully. As treatment-induced inflammation early after therapy can be misinterpreted as vital tumor tissue, it is recommended to wait at least 3 weeks between the last treatment cycle and the subsequent FDG-PET follow-up. Until the results of the prospective multicenter trials “PETAL” and “HD-18” become available, in Germany FDG-PET is only recommended generally for restaging Hodgkin’s disease with a known rest bulk of > 2.5 cm in justifiable individual cases or in clinical trials.